Compensating For The Lack Of Physical Activity In Female Students Through Handball Training - Davronbek Qambarov (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2025)
The study examines the issue of insufficient physical activity among female students and explores the effectiveness of handball training as a compensatory mechanism for improving their physical fitness, health, and psycho-emotional stability. In the context of modern higher education, sedentary learning processes and academic stress significantly reduce students’ physical activity, leading to a decline in adaptive capacity and an increased risk of functional disorders. This research, conducted at Gulistan State University between 2019 and 2022, assessed 102 first-year female students aged 17–19 who had no prior sports training but expressed an interest in handball. Using questionnaires, professionographic analysis, physical and functional assessments, and health diagnostics based on the G.L. Apanasenko method, the study revealed a pronounced deficit of motor activity in the majority of participants. The experiment demonstrated that systematic handball training significantly enhanced the students’ aerobic endurance, motor coordination, and cardiovascular efficiency while improving their social engagement and teamwork skills. The intervention also contributed to the normalization of vital indicators such as lung capacity, muscle strength, and body composition. Data analysis indicated a positive correlation between regular handball training and improvements in physical and mental well-being. Consequently, handball was shown to be an effective pedagogical and recreational tool for counteracting hypokinesia and fostering the holistic development of female students. The findings emphasize the necessity of integrating innovative handball-based training programs into university curricula as a structured approach to promoting health and preventing lifestyle-related diseases among young women. The study highlights that regular participation in sports not only compensates for the lack of physical activity but also supports students’ academic performance and overall quality of life.